Ultrasound Evaluation of the Peroneal Tendons in an Asymptomatic Elite Military Population: A Prospective Cohort Study. (19th February 2020) - Martin, Kevin; Wake, Jeffrey; Van Buren, J Preston
ABSTRACT: Introduction: The purpose of this study was to identify the location of the peroneal tendons in relationship to the fibular groove in an asymptomatic population of elite U.S. Military Service members. Materials and Methods: The peroneal tendons of 41 active duty U.S. Army Rangers were examined. Subjects were placed in a lateral recumbent position with the ankle in a resting neutral position to visualize the tendon in a retromalleolar short-axis view. Maximum active ankle eversion followed by gravity inversion was facilitated while the ultrasound probe was maintained in its original position. Distance from the fibrous lateral ridge of the retromalleolar groove to the anterior aspect of the peroneal brevis was measured in the short axis in neutral, eversion, and inversion. Results: The mean sagittal distance and standard deviation was 0.48 ± 0.9 mm. No subjects demonstrated greater than 1 mm difference between positions, and no dislocations were identified. Side-to-side difference and dominant vs nondominant differences were not statistically significant. Conclusion: The study demonstrates that the distance between the peroneal brevis and the lateral fibular ridge is consistent throughout extremes of motion. These results further the understanding of peroneal tendon function under dynamic examination. Our findings also establish side-to-side consistency prompting a bilateral examination to help identify abnormal pathology.